Raindrop size distribution characteristics in summer of a nival glacial zone in eastern Tianshan, Central Asia - Chen, Puchen; Li, Zhongqin; Wang, Puyu; Yang, Min; Jia, Yufeng; Peng, Jiajia (Frontiers in Earth Science, 2022)
Precipitation is a key component of the hydrological cycle, which is critical to understand its formation and evolution. In this study, the statistical characteristics of the summer raindrop size distribution (DSD) are analyzed by using the observation data of the PWS100 (Present Weather Sensor) located at the meteorological observation site at the terminal of Urumqi Glacier NO.1, eastern Tianshan Mountains. The DSD characteristics of five different rainfall rates and two rainfall types (convective and stratiform) were analyzed for the daytime and nighttime. The average raindrop spectral width was the largest at the class III (1